LB0008 THE EFFECT OF HLA-DRB1 RISK ALLELES ON THE CLINICALEFFICACY OF ABATACEPT AND ADALIMUMAB IN SEROPOSITIVE BIOLOGIC-NAïVE PATIENTSWITH EARLY, MODERATE-TO-SEVERE RA: DATA FROM A HEAD-TO-HEAD SINGLE-BLINDEDTRIAL. (June 2019) - Rigby, William; Buckner, Jane; Bridges, Lou; Nys, Marleen; Gao, Sheng; Polinsky, Martin; Johnsen, Alyssa; Ray, Neelanjana; Bykerk, Vivian
Abstract : Background: Mechanistic differences between biologics are poorly understood. HLA-DRB1 alleles containing the shared epitope (SE), which are strongly associated with RA, are present in 85% of anti-cyclic citrullinated protein 2 (anti-CCP2) + patients (pts) with RA (Jiang et al. Arthritis Rheumatol 2015). In a prior retrospective exploratory analysis, abatacept (ABA) was more effective in SE+ vs SE- pts (Oryoji et al. Ann Rheum Dis 2017). Head-to-head (H2H) comparisons with other agents are lacking. Objectives: This H2H, single-blinded trial (NCT02557100 ) in biologic-naïve pts with early, active RA prospectively explored the relationship between HLA-DRB1 SE and the clinical efficacy of ABA or adalimumab (ADA). Methods: Adults with early (=12 mths from symptom onset), moderate-to-severe RA (ACR/EULAR 2010 criteria) seropositive for anti-CCP2 (>3x ULN) and RF, were randomised 1:1 to SC ABA 125mg wkly or SC ADA 40mg every 2 wks (both with stable, oral MTX wkly) for 24 wks. Pts were grouped by SE status (+/-) based on HLA-DRB1 genotype (-: no SE allele; +: =1 SE allele). Safety was analysed throughout the trial and up to 8 wks post last study drug dose. Clinical efficacy was assessed at Wk24 to determine the proportion of ACR20/50/70 responders in ABA vs ADA arms, and the adjusted mean changes from baseline in DAS28 (CRP), SDAI and CDAI. Treatment (tmt) differences between ABA and ADA in SE+ and SE– pts were assessed for ACR20/50/70 responders and DAS28 (CRP) remission at Wk24. Results: 80 pts were treated: 40 ABA (9 SE-, 30 SE+, 1 SE unknown) and 40 ADA (9 SE-, 31 SE+). Baseline characteristics were balanced. Mean (SD) age, disease duration and DAS28 (CRP) were 46.0 (14.4) years, 5.5 (2.6) mths and 5.2 (1.1), respectively; 75% were female. No new safety signals were identified. In each arm, related AEs (ABA: 12 [30%]; ADA: 11 [27.5%]) and related serious AEs (ABA: 0; ADA: 1 [2.5%]) were similar. Numerically higher efficacy responses were seen with ABA vs ADA at Wk24 (Table 1). Similar results were observed for DAS28 (CRP), SDAI and CDAI. In SE+ pts, numerically higher efficacy responses were seen with ABA vs ADA at Wk24; 95% CI for estimated tmt differences for ACR20/50/70 responses and DAS28 (CRP) remission did not cross 0 (Figure 1). Conclusion: In this seropositive early RA population, numerically higher efficacy responses were seen with abatacept vs adalimumab after 24wks of tmt, with more pronounced tmt differences in SE+ pts. Results are consistent with a previous study in which greater efficacy was seen with abatacept, but not TNF inhibitors, in anti-CCP2+ vs anti-CCP2- pts with RA (Harrold et al. J Rheumatol 2018). Acknowledgement: Marianne Peluso (protocol manager); medical writing: Lola Parfitt (Caudex; funding: BMS) Disclosure of Interests: William Rigby Consultant for: AbbVie, BMS, Genentech and Pfizer, Jane Buckner Grant/research support from: Janssen, Bristol-Myers Squibb (current); Novo Nordisk, Pfizer, Eli Lilly (past), Consultant for: Bristol-Myers Squibb, Eli Lilly, Lou Bridges: None declared, Marleen Nys Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Sheng Gao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Martin Polinsky Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Alyssa Johnsen Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Neelanjana Ray Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Vivian Bykerk Grant/research support from: Mallinckrodt, BMS, Crescendo Biosciences, Sanofi/Regeneron., Consultant for: Amgen, Pfizer, UCB, Scipher, Sanofi/Genzyme/Regeneron